The Written Word in the Medieval Arabic Lands : a Social and Cultural History of Reading Practices - Hirschler, Konrad (Edinburgh University Press, 2012)
The Middle East was one of the most literate civilizations during the high and late medieval period and home to bustling book markets, voluminous libraries and sophisticated book production. After the 'paper revolution' of the 9th and 10th centuries the number of books and the availability of the written word increased dramatically. In the scholarly world the written word played an increasingly prominent role and reading was taken up by wider sections of the population. This book discusses the history of reading in the high and late medieval period in the Middle East in depth. It offers a detailed and wide-ranging analysis of the period, exploring the key themes of literacy/orality/aurality, the teaching of reading skills in schools, and the accessibility and profile of libraries, as well as popular reading practices, often associated with the notion of the illicit. This much-needed overview of the history of reading places the emphasis on the combination of cultural and social history and provides a depth of historical insight to the gradual development of reading practices over the centuries. On the basis of documentary sources and medieval illustrations the book shows in what ways new groups in the Arabic speaking lands, especially craftsmen and traders, started to read and to participate in the written culture between the 12th and the 15th centuries. With this book the late and high medieval periods of Middle Eastern history are finally brought into the burgeoning field of the history of reading.--provided by publisher.